Kelemahan International Criminal Court (ICC) dalam Menangani Kejahatan terhadap Kemanusiaan di Wilayah Palestina (Studi Kasus Konflik Gaza 2023–2024) - Muhammad Makin; Dwi Putri Lestarika (CV WAHANA PUBLIKASI, 2026)
This study examines the structural and political weaknesses of the International Criminal Court (ICC) in responding to alleged crimes against humanity in the Palestinian territories, with a particular focus on the Gaza conflict that began in October 2023. This issue is highly relevant because the ICC formally established its jurisdiction over the Palestinian territories through a decision of Pre-Trial Chamber I in February 2021; however, in practice, legal proceedings have progressed very slowly amid a worsening humanitarian crisis. This research employs a normative legal method with statutory and conceptual approaches, drawing on an analysis of the Rome Statute (1998), ICC and International Court of Justice decisions, as well as Indonesian national legal instruments. Four key weaknesses are identified in this study. First, jurisdictional limitations arise because Israel has not ratified the Rome Statute, although territorial jurisdiction remains applicable. Second, the absence of an enforcement mechanism renders arrest warrants difficult to execute. Third, increasing political pressure from the United States further constrains the Court’s effectiveness. Fourth, the ICC’s procedural timeline is often prolonged and inefficient. The issuance of arrest warrants against Benjamin Netanyahu and Yoav Gallant in November 2024 represents a historic precedent while simultaneously exposing the fragility of the existing international criminal justice system.This study further examines Indonesia’s legal position through Article 28A and Article 28I of the 1945 Constitution of Indonesia, as well as Law No. 39 of 1999 on Human Rights. It argues that Indonesia’s normative commitments must be translated into more concrete diplomatic actions, including the ratification of the Rome Statute.